Crop resistance and household resilience – the case of cassava and sweetpotato during super-typhoon Ompong in the Philippines - Gatto, M.; Naziri, D.; San Pedro, J.; Béné, Christophe (Elsevier, 2021)
Extreme weather events can have devastating effects on agricultural production. As rural households in developing countries largely depend on agriculture, climatic shocks have the potential to undermine food security. In this paper, we explore how crop resistance contribute to household resilience in extreme weather events. As case study, we used cassava and sweetpotato, two root and tuber crops (RTCs), in the context of super-typhoon Ompong that wreaked havoc in the northern parts of the Philippines in 2018. Primary data were collected from 423 households who were affected by the super-typhoon. Methodologically, we employed a multivariate probit model to jointly estimate various household disaster responses, and applied propensity score matching techniques to control for potential endogeneity. The findings suggest that RTCs can contribute to households’ resilience capacity due to their resistance to climatic shocks being underground crops. In addition, RTCs appear to be important in influencing the households’ responses to typhoon. Our findings suggest that RTC cultivation reduces the need to resort to negative coping strategies, such as using household savings and requesting assistance from neighbors and friends, and that higher consumption of sweetpotato is linked to longer spells of reduced mobility. Furthermore, in the case of super-typhoon Ompong, affected households exploited the short production cycle of sweetpotato and cassava and planted them in the typhoon aftermath, a strategy that help to gain faster and earlier access to food. Based on these findings some policy recommendations are proposed.